(untitled) - Kouzes, James M. (San Francisco, 1995)
In the 1980s and again in the '90s, James M. Kouzes and Barry Z. Posner published The Leadership Challenge to address issues they uncovered in research on ordinary people achieving "individual leadership standards of excellence." The keys they identified--model the way, inspire a shared vision, challenge the process, enable others to act, encourage the heart--have now been reexamined in the context of the post-millennium world and updated in a third edition. "What we have discovered, and rediscovered, is that leadership is not the private reserve of a few charismatic men and women," write Kouzes, chairman emeritus of the Tom Peters Company, and Posner, dean of the Leavey School of Business at Santa Clara University. "People make extraordinary things happen by liberating the leader within everyone." After explaining their concept and methodology, the authors detail the five essentials noted above in a pair of chapters apiece that bring clarity to their theories with case studies and recommended actions. The specificity of each (motivating through "the meaningfulness of the challenge, not the material rewards of success," for example, and being able to "accept the mistakes that result from experimentation") is enhanced by advice on sustaining the commitment and making leadership skills accessible to all. The results remain as relevant as when they were first published
Keywords: Leadership,Executive ability,Management